Nursing informatics skills relevance and competence for final year nursing students. - Chipps, Jennifer; le Roux, Loretta; Agabus, Jakobina; Bimerew, Million (Curationis, 2022)
Background: The increasing use of technology in nursing practice requires nursing students to be competent in nursing informatics with an attitude of acceptance of technology in the healthcare environment. Objectives: The objectives of the study were to determine final year nursing students' perceptions and skills in nursing informatics and their attitudes towards computerisation in nursing practice. Method: The study population were 198 final year nursing students from a selected university in the Western Cape, South Africa. All-inclusive sampling was used. A descriptive survey was conducted using a self-administered questionnaire which included two validated scales, namely the validated Nursing Informatics Competency Assessment Tool (NICAT) and the Nurses' Attitudes towards Computerisation scale. Means and 95% confidence intervals (CI) of the ratings of the perceived relevance of nursing informatics skills in nursing practice, perceived levels of competence in nursing informatics skills and attitudes towards computers were calculated. Results: A total of 91 undergraduate respondents completed the survey. Computer literacy skills were rated overall as most relevant (4.23, 95% confidence interval [95% CI]: 4.06–4.40) and the skills perceived most competent (4.16, 95% CI: 3.81–4.22). The respondents had an overall positive score for attitudes towards computerisation in healthcare (67.34, s.d. = 10.40, 95% CI: 65.18–69.51). Conclusion: The study concluded that computer literacy skills, informatics literacy skills and information management skills were relevant to nursing practice, despite varying levels of competence in these skills among nurses. Contribution: What key insights into the research results and its future function are revealed? How do these insights link to the focus and scope of the journal? It should be a concise statement of the primary contribution of the manuscript; and how it fits within the scope of the journal.